PUGS: A novel scale to assess perceptions of uncertainties in genome sequencing. Issue 2 (30th January 2017) - Biesecker, B.B.; Woolford, S.W.; Klein, W.M.P.; Brothers, K.B.; Umstead, K.L.; Lewis, K.L.; Biesecker, L.G.; Han, P.K.J.
Abstract : Expectations of results from genome sequencing by end users are influenced by perceptions of uncertainty. This study aimed to assess uncertainties about sequencing by developing, evaluating, and implementing a novel scale. The Perceptions of Uncertainties in Genome Sequencing (PUGS) scale comprised ten items to assess uncertainties within three domains: clinical, affective, and evaluative. Participants ( n =535) from the ClinSeq® NIH sequencing study completed a baseline survey that included the PUGS; responses (mean = 3.4/5, SD =0.58) suggested modest perceptions of certainty. A confirmatory factor analysis identified factor loadings that led to elimination of two items. A revised eight‐item PUGS scale was used to test correlations with perceived ambiguity ( r = −0.303, p < 0.001), attitudinal ambivalence ( r = −0.111, p = 0.011), and ambiguity aversion (r = −0.093, p = 0.033). Results support nomological validity. A correlation with the MICRA uncertainty subscale was found among 175 cohort participants who had received results ( r = −0.335, p < 0.001). Convergent and discriminant validity were also satisfied in a second sample of 208 parents from the HudsonAlpha CSER Project who completed the PUGS (mean = 3.4/5, SD = 0.72), and configural invariance was supported across the two datasets. As such, the PUGS is a promising scale for evaluating perceived uncertainties in genome sequencing, which can inform interventions to help patients form realistic expectations of these uncertainties. Abstract :